The book of Genesis composition, reception, and interpretation - Evans, Craig A.; Lohr, Joel N.; Petersen, David L. (Leiden : BRILL, 2012)
Drawing on the latest in Genesis scholarship, this volume offers twenty-nine essays on a wide range of topics related to Genesis, written by leading experts in the field. Topics include its formation, reception, textual history and translation, themes, theologies, and place within Judaism, Christianity, and Islam.
Genesis, The Qur'an and Islamic Interpretation (Carol Bakhos)Part Four. Genesis and Theology; The Theology of Genesis (Joel S. Kaminsky); Genesis in the Context of Jewish Thought (Marvin A. Sweeney); Genesis and Ecology (Terence E. Fretheim); Indices; Scripture and Other Ancient Writings; Modern Authors.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, Textual; Bible. -- Criticism, Redaction; Bible. -- Criticism, Textual; Bible. -- Versions; Bible. -- Criticism, Textual; RELIGION / Biblical Studies / Old Testament; Electronic books